Crystal structure of bis(μ(2)-triphenylacetato-κO:κO′)bis(diisobutylaluminium) - Vinogradov, Alexander A. (Acta Crystallogr E Crystallogr Commun, 2019)
Single crystals of the title compound, [Al(iBu)(2)(O(2)CCPh(3))](2) or [Al(2)(C(4)H(9))(4)(C(20)H(15)O(2))(2)], have been formed in the reaction between tris(tetrahydrofuran)tris(triphenylacetato)neodymium, [Nd(Ph(3)CCOO)(3)(THF)(3)], and triisobutylaluminium, Al(iBu)(3), in hexane followed by low-temperature crystallization (243 K) from the reaction mixture. The structure has triclinic (P [Image: see text]) symmetry at 120 K. The dimeric complex [Al(iBu)(2)(O(2)CCPh(3)-μ-κO:κO′)](2) is located about an inversion centre. The triphenylacetate ligand displays a μ-κO:κO′-bridging coordination mode, leading to the formation of an octagonal Al(2)O(4)C(2) core. The complex displays H(Ph)⋯C(Ph) intermolecular interactions.